The Function Of Social Media In Conventional Media Journalis In North Sumatra - Farhan Indra; Tri Praise Panggabean (CV. AFDIFAL MAJU BERKAH, 2023)
This digital age, the latest media advances Already give birth to order journalism latest aim journalism residents informed by residents general No journalist reliable. various type category means the latest, exclusively social media, already open chance for public normal. Follow and deep procedure submission of data as origin suggestion information to public broad. Journalism inhabitant grow fast in fame as well as hinted with consuming content. Journalism inhabitant as product news broadcast in the mass media conventional. Product journalism inhabitant Can present missing data from information conventional media news That distributed to the crowd as information items. this writing mean, to view method utilise social media to use support business journalism inhabitant as well as consequence utilization journalism residents on the means conventional. study that used ie Method qualitative utilise method review literature. From the results review, means conventional mass media a number of big liked as effect from reportage correspondence resident at least famous for inhabitant to use looking for linked data information journalism citizen. But growth journalism inhabitant instead without problem application ethics journalism often No practiced because journalism inhabitant lived by ordinary people who do not background behind journalism